Improved Control Method to Reduce the Voltage and Current Harmonics in a Microgrid Subjected to Non-linear Load Conditions - Khidrani, Attaullah; Habibuddin, M; Paend Bakht, Muhammad; Hamza Sule, Aliyu; Haider, Raza (International Journal of Engineering and Technology, 2018)
For the past few decades, the distributed renewable energy sources (RES) have become the main alternative to centralized power generation system, mainly due to economic and environmental concerns. The two major problems in employing this RES are the severe current harmonic contents in their output current and the imbalance in system voltage and current. Accordingly, this research work presents a method to minimize the current and voltage harmonic contents in a three-phase hybrid photovoltaic (PV) and wind turbine (WT) Grid Connected Inverters (GCI) subjected to nonlinear and unbalanced load conditions. The proposed method effectively offsets the harmonic contents in voltage and current of the system under study without relying on additional equipment, including passive and active filters. The obtained results reveal the effectiveness of proposed control strategy in reducing the total harmonic distortion (THD) while simultaneously correcting any imbalance in the system. The newly developed method, which features the GCI inverters using synchronous reference frame (SRF), proved itself to be very effective, as evident from the simulation results obtained.Â Â